Rare bird documentation form for Red-necked Phalarope north of Lake View, 1996 - Thelen, Robet al (1996)
Rare bird documentation form for a Red-necked Phalarope north of Lake View in Sac County, IA on April 26, 1996. Epson - sheet feed